2014 19th IEEE-NPSS Real Time Conference 2014
DOI: 10.1109/rtc.2014.7097480
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Data Acquisition System for an endoscopic PET-US detector

Abstract: Abstract-According to current prognosis studies of pancreatic cancer, survival rate nowadays is still as low as 6% mainly due to late detections. Taking into account the location of the disease within the body and making use of the level of miniaturization in radiation detectors that can be achieved at the present time, EndoTOFPET-US collaboration aims at the development of a multimodal imaging technique for endoscopic pancreas exams that combines the benefits of high resolution metabolic information from Time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…For the first case, there are important examples, such as experiments inside particle accelerators, for instance A Toroidal LHC ApparatuS (ATLAS) experiment; 1,2 telescopes, such as Large High Altitude Air Shower Observatory (LHAASO), 3 Square Kilometer Array (SKA) 4 and SKA's precursor Karoo Array Telescope (MeerKAT), 5 and applications in health sciences. 6 On the other hand, some industrial applications can be found in the framework of Internet of things or Smart Grids. All of these cases correspond with DACQ systems that share distributed sensor networks scattered over the facility.…”
Section: Introductionmentioning
confidence: 99%
“…For the first case, there are important examples, such as experiments inside particle accelerators, for instance A Toroidal LHC ApparatuS (ATLAS) experiment; 1,2 telescopes, such as Large High Altitude Air Shower Observatory (LHAASO), 3 Square Kilometer Array (SKA) 4 and SKA's precursor Karoo Array Telescope (MeerKAT), 5 and applications in health sciences. 6 On the other hand, some industrial applications can be found in the framework of Internet of things or Smart Grids. All of these cases correspond with DACQ systems that share distributed sensor networks scattered over the facility.…”
Section: Introductionmentioning
confidence: 99%